Assessment of bariatric surgery results - Lívia Moreira Barros; Natasha Marques Frota; Rosa Aparecida Nogueira Moreira; Thiago Moura de Araújo; Joselany Áfio Caetano
The objective was to evaluate the results of bariatric surgery in patients in the late postoperative period using the Bariatric Analysis and Reporting Outcome System (BAROS). This cross-sectional study was conducted from November 2011 to June 2012 at a hospital in the state of Ceará, Brazil. Data were collected from 92 patients using the BAROS protocol, which analyzes weight loss, improved comorbidities, complications, reoperations and Quality of Life (QoL). Data were analysed using the chi-squared test, Fischer's exact test and the Mann-Whitney test. There was a reduction in the Body Mass Index (47.2 ± 6.8 kg/m2 in the pre-operatory and 31.3 ± 5.0 kg/m2 after surgery, p< 0.001). The comorbidity with the highest resolution was arterial hypertension (p<0.001), and QV improved in 94.6% of patients. The main complications were hair loss, incisional hernia and cholelithiasis. The surgery provided satisfactory weight loss and improvements in the comorbidities associated to a better QL. Use of the BAROS protocol allows nurses to plan interventions and maintain the good results.